Peak and low flow investigation of Benguet mountainous river catchments - Macabiog, Rafael B. (1995)
Streamflow estimation has been the subject of considerable attention by many different private and government organizations involved int he development of water resource projects. Several techniques and approaches have been utilized in dealing with ungaged catchments or catchments of inadequate flow records. It was observed that factors directly and indirectly related to flow characteristics are good measures for derivation. These factors vary with topography, climate, morphology, geology, and land use. This thesis deals on investigating the peak and low flow characteristics of Benguet's mountainous river catchments. A number of stations within mountainous region with adequate flow records were used to derive several flow characteristics. The flow characteristics considered were the average daily flow, flow availability magnitudes, flood frequency magnitudes and the base flow index. Likewise, the unit hydrograph of selected catchments within the study area were also derived. The flow availability magnitudes or commonly illustrated as the flow duration curves were computed by transforming the daily flows into percentages of the average daily flows. The flow magnitudes at 25, 50, 75, and 95 percent of time availability were derived from the computed flow duration curves. The average daily flow is the mean of all the daily flows recorded at that station. The annual maximum daily flows derived from the streamflow data gathered were analyzed using frequency distributions, such as the Normal Distribution, Type 1 Extremal Distribution, Two Parameter Log Normal Distribution, Three Parameter Log Normal Distribution, Pearson Type III Distribution and the Log Pearson Type III Distribution. The best fit frequency distribution was used to compute for the flood frequency magnitudes at return periods of 2,5,10,15,20 and 25. The Unit Hydrograph was derived using the recorded hourly flows and rainfall at the selected catchments. Observations were conducted for every occurrence of a significant typhoon within the year.
Factors defined by the basin characteristics were derived from the stations used to evaluate flow characteristics. These include the drainage area, average annual rainfall, circularity ratio, main channel length, main channel slope, basin perimeter, stream frequency, drainage density, basin elevation, maximum basin relief, geology, soil and land use. They were analyzed using maps, records and figures gathered from several agencies. Prediction models were derived in this study to estimate flow characteristics of an ungaged catchment within the region or of catchment with similar site specific characteristics. The flow characteristics were the dependent variables and the basin characteristics served as the predictors in the analyzed model. The study showed that some of the basin characteristics were significant and served as a good measure. The prediction model for the flood frequency magnitude revealed a dependence on the area extensive variable such as the drainage area and the main channel length. Included also is the measure of stream frequency. The flow duration curves were predicted from the area extensive variables. The base flow indices were dependent on the geology of the basin. IT showed that base flow is directly proportional to the perme4ability of the rock structure within the basin. Basins lying on a more permeable rock structure were more likely to produce greater base flow discharge.
Computer print-out.
Thesis (M.S.)--University of the Philippines, Diliman.
Keywords: Streamflow -- Philippines -- Benguet; Hydrological forecasting -- Philippines -- Benguet; River engineering -- Philippines -- Benguet